Preclinical Evaluation of the Antihypertensive Effect of an Aqueous Extract of Anogeissus leiocarpa (DC) Guill et Perr. Bark of Trunk in L-NAME-Induced Hypertensive Rat - Belemnaba L; Nitiéma M; Ilboudo S; Ouédraogo GG; Ouédraogo N; Belemlilga MB; Compaoré S; Ouédraogo S; Ouédraogo S (Dove Medical Press, 2021)
Lazare Belemnaba,1 Mathieu Nitiéma,1 Sylvain Ilboudo,1 Gueswindé Geoffroy Ouédraogo,1 Noufou Ouédraogo,1 Mohamed Bonewendé Belemlilga,1 Souleymane Compaoré,1,2 Salfo Ouédraogo,1,2 Sylvin Ouédraogo1 1Institut de Recherche en Sciences de la Santé/Centre National de la Recherche Scientifique et Technologique (IRSS/CNRST), 03 BP 7047, Ouagadougou, 03, Burkina Faso; 2Université Joseph KI-ZERBO, 03 BP 7021, Ouagadougou, 03, Burkina FasoCorrespondence: Lazare BelemnabaResearch Institute for Health Sciences (IRSS), Department of Medicine and Traditional Pharmacopeia (MEPHATRA/Ph), National Centre for Scientific and Technological Research (CNRST), 03 BP 7047, Ouagadougou, 03, Burkina FasoTel +226 25 36 33 64/25 36 32 15Fax +226 25 36 28 38/25 36 03 94Email lbelemnaba2@gmail.comBackground: The present study investigates the effect of an aqueous extract of Anogeissus leiocarpa (AEAL) on normotensive Wistar rats and its chronic antihypertensive effects in L-NAME-induced hypertensive rats by using a non-invasive tail-cuff model.Methods: The effects of AEAL (50mg/kg) and NaCl 0.9% on blood pressure were investigated by daily oral administration in normotensive Wistar rats over four weeks. L-NAME-induced hypertensive rats were produced by L-NAME (40mg/kg) daily oral administration for two weeks. For chronic antihypertensive effects, induced hypertensive rats have received L-NAME in combination with AEAL (10 or 50mg/kg/day) for two following weeks.Results: In normotensive rats, daily administration of AEAL (50mg/kg) has no significant effect on their blood pressure, which was similar to that of the control group. L-NAME's daily oral administration induces a progressive increase in systolic blood pressure (SBP) from 115.8 ± 7.9mmHg to 153.5 ± 4.6mmHg after two weeks, which was maintained to the end of the treatment. In L-NAME-induced hypertensive rats, AEAL (50mg/kg/day) significantly decreases the SPB from 160.0 ± 5.8 mmHg to 108.8 ± 2.7mmHg after only four days of administration. However, the lower dose of AEAL (10mg/kg) also normalized the SBP of L-NAME-induced hypertensive rats but only evident after seven days of administration. Moreover, AEAL does not effect on the serum biochemical parameters (ALAT, ASAT, CREAT, etc.) and any macroscopic adverse effect was detected on the sensible organs involved during hypertension. In the aorta rings from treated rats, AEAL (50mg/kg/day) alone or in combination with L-NAME has enhanced the vasodilation effect of acetylcholine. However, the vasodilation effect of AEAL alone or in association with L-NAME has enhanced the sodium nitroprusside effect in treated rat aorta rings after autopsy.Conclusion: These findings suggest that AEAL affords significant antihypertensive effects against L-NAME-induced hypertensive rats without modification of serum parameters and deleterious effects.Keywords: Anogeissus leiocarpa, non invasive, L-NAME-induced hypertension, vasorelaxation